Severe, diffuse coronary artery spasm after drug-eluting stent placement - Brott, Brigitta C.; Chapman, Gregory D.; Anayiotos, Andreas (My University, 2006)
OBJECTIVES: Three cases of severe, diffuse coronary artery spasm after drug-eluting stent placement at our institution prompted this review. BACKGROUND: Drug-eluting stents have gained widespread use due to extraordinarily low rates of restenosis. Despite these generally superior clinical outcomes, the specter of rare idiosyncratic reactions remains a concern. METHODS: We performed searches of Medline and the U.S. FDA Manufacturer And User facility Device Experience database (MAUDE) to identify and describe spasm after coronary stent placement. Searches included drug-eluting and bare-metal stents. Institutional cases are reviewed. Location, time course and outcome of cases are described. RESULTS: Thirteen cases of spasm were identified after stent placement. Seven cases occurred after Cypher™ drug-eluting stent placement, 2 after Taxus® drug-eluting stent placement, 1 after BiodivYsio™ and 3 after bare-metal stents. Five patients experienced diffuse, multivessel spasm, 2 after Cypher, 2 after Taxus, and 1 after a Velocity™ stent. Of these 5 patients, 2 died. An additional 2 required intra-aortic balloon pump placement for cardiogenic shock. Another had persistent symptomatic, diffuse coronary spasm documented by angiography at 1 year. CONCLUSIONS: We describe coronary spasm after stent placement, particularly after drug-eluting stents. Outcomes associated with diffuse severe spasm after stenting are poor, and the pathophysiology remains poorly understood.
Keywords: Nitroglycerin; Heparin; Angiocardiography; Coronary artery